Simulating Non-Functional Communication Requirements in Automotive Software - Pestana, Larissa; Miranda, Breno (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST), 2025)
This paper proposes an approach to support the early validation of non-functional communication requirements in the development of automotive embedded software, particularly for Advanced Driver Assistance Systems (ADAS) that incorporate V2X (Vehicle-to-Everything) communication as a complementary input. The approach integrates the ns-3 network simulator as a systematic tool during the initial stages of the V-model, focusing on the data link layer, specifically the MAC and PHY sublayers, using the IEEE 802.11p protocol and its evolution, IEEE 802.11bd. Simulations are conducted in parallel with requirements elicitation, enabling the assessment and refinement of key parameters such as latency, reliability, packet loss, and communication range. By anticipating the analysis of these properties through simulation, the approach aims to reduce rework in later verification phases and improve the definition of system architecture. The ns-3 environment offers a reproducible, scalable, and low-cost solution for evaluating communication behavior under adverse conditions, contributing to more informed decisions early in the automotive software lifecycle.